Voyages that have been attempted to discover a northern passage to the Pacific Ocean [electronic resource] - Wyld, J. (James), 1790-1836 ([S.l.] : Printed from stone in the Quarter Masr. General's Office, Horse Guards, 1818)
The text lists and very briefly describes Arctic voyages from 1497 to 1818. Electronic reproduction. Mode of access: Internet. 44